Cardiac pacing and ICDs - Ellenbogen, Kenneth A; Wood, Mark A (Blackwell Science, 2002)
The latest edition of this guide to heart pacing is a must have for cardiologists, residents, EP nurses and electrophysiologists. Cardiac Pacing, 3/e is a highly readable and comprehensive guide to the basic concepts and clinical techniques of heart pacing. Covers indications, hemodynammics, implantation, and patient follow-up Portable size makes it ideal to carry on rounds Numerous illustrations give the reader an instant picture of concepts and topics Be prepared by emergencies and complications after reading the section on troubleshooting and follow-up care
Keywords: Pacemaker, Artificial; kardiostimulátor; Heart Diseases; kardiologie; nemoci srdce